2019
DOI: 10.1177/0300060519856505
|View full text |Cite
|
Sign up to set email alerts
|

miR-16 regulates proliferation and invasion of lung cancer cells via the ERK/MAPK signaling pathway by targeted inhibition of MAPK kinase 1 (MEK1)

Abstract: ObjectiveThe ERK/MAPK signaling pathway regulates cell proliferation and invasion. MAPK kinase 1 (MEK1) is a protein kinase upstream of ERK that can activate the pathway. Expression of microRNA (miR)-16 in lung cancer tissues is decreased. The aim of this study was to determine roles of miR-16 in proliferation and invasion of lung cancer cells.MethodsWe used a luciferase reporter assay to determine a regulatory relationship between miR-16 and MEK1 and assessed expression of MEK1 in normal lung cells and lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“… 41 Decreased MIR-16 expression upregulates expression of MEK1 , which in turn promotes cancer cell invasion and proliferation. 42 Overexpression of MIR-16 downregulates the ERK/MAPK pathway by inhibiting MEK1 expression. Consequently, this reduces clone formation and inhibits cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Decreased MIR-16 expression upregulates expression of MEK1 , which in turn promotes cancer cell invasion and proliferation. 42 Overexpression of MIR-16 downregulates the ERK/MAPK pathway by inhibiting MEK1 expression. Consequently, this reduces clone formation and inhibits cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…miR-16-5p resides on chromosome 13q14, which is generally deleted in B cell chronic lymphocytic leukemia (22). miR-16-5p is also dysregulated in several cancer types, such as gastric cancer, breast cancer and lung cancer (31,48,49). In prostate cancer (PCa), the 13q allele deletion has also been reported, and the frequency of this is associated with tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we examined the abundance of four selected differentially expressed miRNAs (miR-16, miR-181a-3p, miR-223, miR-451) by real-time qPCR in the liver of silver carp exposed for 1, 3, 6, and 12 h to MC-LR (50 and 200 µg/kg); miR-16 was found to act as a tumor suppressor associated with the development of chronic lymphocytic leukemia, breast cancer, lung cancer, and colorectal cancer [46,47]. Accumulated evidence has shown that the expression of miR-16 is decreased in multiple cancer cells, and elevated expression of miR-16 significantly inhibits the proliferation of cancer cells and induces G0/G1 cell cycle arrest [48]. miR-181a plays a key role in the immune response by regulating T cells [49,50].…”
Section: Discussionmentioning
confidence: 99%